Respuesta :
Answer:
Option C. is the correct option.
Step-by-step explanation:
Clara found the product of (3 - 6y²) and (y² + 2) and she did it as below
(3 - 6y²)(y² + 2) = 3(y²) + (-6y²)×2 = 3y² - 12y² = -9y²
She did the step wrong as highlighted above. She did not use the distributive property correctly.
Now we will do it in a correct way.
(3 - 6y²)(y²+2) = 3(y² + 2) - 6y²(y² + 2)
= [tex]3y^{2}+6-6y^{4}-12y^{2}=-6y^{4}-9y^{2}+6[/tex]
Therefore Option C. is the correct answer.
The product of (3 - 6y²) and (y² + 2) is -6y⁴ - 9y² + 6
Product
Finding the product between two values is multiplying the values together .Therefore, the product between (3 - 6y²) and (y² + 2) is as follows:
- (3 - 6y²)(y² + 2)
(3 - 6y²)(y² + 2) = 3(y²) + 3(2) - 6y²(y²) - 6y²(2)
Therefore,
3(y²) + 3(2) - 6y²(y²) - 6y²(2) = 3y² + 6 - 6y⁴ - 12y²
3y² + 6 - 6y⁴ - 12y² = -6y⁴ - 9y² + 6
Therefore, the product of (3 - 6y²) and (y² + 2) is -6y⁴ - 9y² + 6
learn more on product here: https://brainly.com/question/4023604?referrer=searchResults